Finnish supervised probationary freedom as support for a desistance from crime - Järveläinen, Eeva (European journal of probation, 2024)
Electronic monitoring enables different, more transparent and open ways of enforcing sentences. This study examines Finnish Supervised Probationary Freedom (SPF) from the perspective of a desistance from crime. We analyze what meanings sentenced people give to SPF in terms of their desistance from crime, adopting the viewpoints of moderate social constructionism and rhetorical analysis. The research data was collected from interviews of 26 people who had experience with SPF. According to the results, SPF supervision and participation in SPF activities can create a framework for practicing a crime- and drug-free life. The person’s own desire to desist is the starting point. Support provided by prison and probation employees appears to be central to the construction of a new identity. Support from social work is necessary to complete SPF, and NGO support enhances reintegration into society during the SPF. However, the opportunities on offer for reentry are limited.